Social capital as the factor of the state configuration of the market of the republic of Belarus - Ostroga, Viktor; Zhukovskaya, Olga (Business, Management and Economics Engineering, 2011)
In the article social capital as the factor of social and economic exchange optimization (transactional costs decrease), configuration of the market and system of economic interests of the Republic of Belarus in the context of the history of this social and economic phenomenon research, the place and role of state regulation in economic processes and modern understanding of the market in correlation with economic growth and national safety is considered. Also the influence of social capital on the market system of Belarus and mechanisms of this social and economic phenomenon usage with the view of market functioning perfection is analyzed under the conditions of national and global imperatives.